Eça de Queirós e Euclides da Cunha: interdiscursividade jornalístico-literária - Costa, Andreia Rosmaninho (2008)
This investigation presents as its aim proving that there was an aesthetic improvement process in the journalistic productions from which O Egipto, by Eça de Queirós, and Os Sertões, by Euclides da Cunha, have derived. Taking such works as high level journalistic-literary productions in expression, we mean to study the paths taken by the authors searching for an artistic improvement of primary texts, viewing the production of works accepted by the literary canon. Keeping this in mind, taking as a basis the interdiscursive theory and the systematization of certain peculiarities of Literary Journalism, by Norman Sims. Thus, the study examines the literary content in these works, meaning to evaluate the aesthetic and thematic levels in them, with the intention to confirm the thesis that in such examples of journalistic practice happens an important association between thought and expression, as well as it is possible to verify the constitution of broad development both in artistic potentiality and ideological virtualities in the text. Recognizing that the subjects which originated the works passed through transformation and transposition processes in what concerns not only the formal but also the content aspects this study applies to the examination of the referred evolutions which culminate in the production of works recognized as reference productions of historical, scientific, artistic and literary characters. The applied methodology is based on a comparative analysis of the initial versions from O Egipto and Os Sertões, published by daily media press, and a selection of their equivalent passages in their literary versions. We mean to demonstrate that, besides the idea that both versions have a review posture in conceptual terms, there is always an important preoccupation viewing the retaking of a journey towards the literary elevation of the text, once it is possible to recognize, in the last editions, the existence of an aesthetic development of the queirosian and euclidean thoughts. The theme of the present research is, so, the ethic and aesthetic realignment which gave origin to artistic productions in which form and content are priorized in a balanced way.